Finansowe metody pomiaru aktywów niematerialnych - Michalczuk, Grażyna (Financial Methods of Intangible Assets Measurements, 2008)
To achieve success, not only should the company have intangible assets difficult to copy, but also it should have an ability to use them in a practical way to a greater extent as well as have the ability of sustained raising and accumulating such assets. Hence, possessing extensive knowledge of the essence of separate intangible assets and devices allowing their measurement seems to be indispensable. Presented methods of intangible assets measurements in this article: IVM™, TVCV and TVETM , belong to so-called methods of direct intangible assets measurements, allowing to estimate the monetary value of individual components of intellectual capital. However, the practical application of such systems requires taking earlier action to increase level of involvement and preparations of management personnel for intangible assets management in a company. The effectiveness of such action is determined mainly by the management personnel understanding the significance of non- material resources in creating company value.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 392-402